AMP-Activated Protein Kinase (AMPK) Is Activated in Muscle of Subjects With Type 2 Diabetes During Exercise - Musi, Nicolas; Fujii, Nobuharu; Hirshman, Michael F.; Ekberg, Ingvar; Fröberg, Sven; Ljungqvist, Olle; Thorell, Anders; Goodyear, Laurie J. (Diabetes (New York, N.Y.), 2001)
AMP-Activated Protein Kinase (AMPK) Is Activated in Muscle of Subjects With Type 2 Diabetes During Exercise Nicolas Musi 1 , Nobuharu Fujii 1 , Michael F. Hirshman 1 , Ingvar Ekberg 2 , Sven Fröberg 2 , Olle Ljungqvist 2 3 , Anders Thorell 2 and Laurie J. Goodyear 1 1 Research Division, Joslin Diabetes Center and Department of Medicine, Brigham and Women’s Hospital and Harvard Medical School, Boston, Massachusetts 2 Karolinska Institute, Centre of Gastrointestinal Disease, Ersta Hospital, Stockholm, Sweden 3 Department of Surgery, Huddinge University Hospital, Huddinge, Sweden Abstract Insulin-stimulated GLUT4 translocation is impaired in people with type 2 diabetes. In contrast, exercise results in a normal increase in GLUT4 translocation and glucose uptake in these patients. Several groups have recently hypothesized that exercise increases glucose uptake via an insulin-independent mechanism mediated by the activation of AMP-activated protein kinase (AMPK). If this hypothesis is correct, people with type 2 diabetes should have normal AMPK activation in response to exercise. Seven subjects with type 2 diabetes and eight matched control subjects exercised on a cycle ergometer for 45 min at 70% of maximum workload. Biopsies of vastus lateralis muscle were taken before exercise, after 20 and 45 min of exercise, and at 30 min postexercise. Blood glucose concentrations decreased from 7.6 to 4.77 mmol/l with 45 min of exercise in the diabetic group and did not change in the control group. Exercise significantly increased AMPK α2 activity 2.7-fold over basal at 20 min in both groups and remained elevated throughout the protocol, but there was no effect of exercise on AMPK α1 activity. Subjects with type 2 diabetes had similar protein expression of AMPK α1, α2, and β1 in muscle compared with control subjects. AMPK α2 was shown to represent approximately two-thirds of the total α mRNA in the muscle from both groups. In conclusion, people with type 2 diabetes have normal exercise-induced AMPK α2 activity and normal expression of the α1, α2 and β1 isoforms. Pharmacological activation of AMPK may be an attractive target for the treatment of type 2 diabetes. Footnotes Address correspondence and reprint requests to Laurie J. Goodyear, PhD, Research Division, Joslin Diabetes Center, One Joslin Place, Boston, MA 02215. E-mail: Laurie.Goodyearatjoslin.harvard.edu . Received for publication 21 December 2000 and accepted in revised form 14 February 2001. Posted on the World Wide Web at www.diabetes.org/diabetes on 16 March 2001. ACC, acetyl-CoA carboxylase; AICAR, 5-aminoimidazole-4-carboxamide ribonucleoside; AMPK, AMP-activated protein kinase; AMPKK, AMPK kinase; DTT, dithiothreitol; FFA, free fatty acid; PI, phosphatidylinositol; PCR, polymerase chain reaction; RT, reverse transcriptase; TBST, Tris-buffered saline with Tween; W max , maximum workload; ZMP, 5-aminoimidazole-4-carboxamide ribonucleotide.